The use of ICT for teaching historical-astronomical aspects: Galileo’s discoveries - Pérez-Rodríguez, Uxío; Lorenzo-Rial, María; Castiñeira-Rodríguez, Nuria; Varela-Losada, Mercedes (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
When considering the implementation of activities related to the teaching of astronomical aspects, there are obvious practical problems that do not help to develop an adequate school science activity. ICT are a very useful tool for overcoming these difficulties, since they make it possible to reproduce celestial phenomena and experiment with them. The aim of this article is, in particular, to reflect on the usefulness of computer simulations for teaching historical-astronomical aspects. As an example of their possibilities, simulations that can be used to visualise various astronomical phenomena discovered by Galileo Galilei are presented.